Trends in sediment yield of the Kemaman River Estuary, Terengganu- Disember 2002-February 2004 - Toriman, Mohd Ekhwan; Juahir, Hafizan; Mokhtar, Mazlin; M. Zain, Sharifuddin (2004)
The Kemaman River drains the southern half of Kemaman Chendor coastal system and is the primary source of sediment to Kemaman estuary. In this paper, it is demonstrated that anthropogenic activity within a watershed, such as agriculture and urbanization were affect the sediment yield from the watershed. Over 26 month, the delivery of suspended sediment from the Kemaman River to The Kemaman Estuary has increase by about 25 percent. Using flow and suspended sediment discharge data provided by the Drainage and Irrigation Department (DID) revealed possible increasing trend on suspended sediment discharge and concentration. Temporal analysis indicates that the trend of sediment yield was increase during the monsoon season resulting over sediment supply closed to river mouth. This scenario has implication for nearshore fisherman's navigation due to seabed deposition. In a broader context, this study underscores the need to address the anthropogenic impacts and flood monsoon on sediment yield in the Kemaman-Chendor estuary system.